Outcomes Following Operative Treatment of Adolescent Mallet Fractures. Issue 1 (February 2018) - Chen, Andrew T.; Conry, Keegan T.; Gilmore, Allison; Son-Hing, Jochen P.; Liu, Raymond W.
Background: Many surgeons advocate for surgical intervention of adult mallet fractures that involve either subluxation of the distal interphalangeal (DIP) joint or those that involve more than one-third of the articular surface. However, the efficacy of operative treatment and complication rates are unclear regarding the adolescent population. Questions/Purposes: The goal of this study is to evaluate the clinical outcomes following operative fixation of bony mallet fractures in the adolescent population. Methods: Seventeen patients with bony mallet fractures treated surgically were retrospectively reviewed. Twelve patients were treated by closed reduction with extension block pinning. The other patients underwent an open reduction and pin fixation. The average age was 15.2 years (13–18). Most injuries were sport related. The average time from injury to presentation was 17 days and from injury to surgery was 24.5 days. Nine patients had subluxation at the DIP joint and all involved at least one-third of the articular surface. Results: The average time from surgery to pin removal was 28 days (19–46). All distal phalanx physis were closed or nearly closed. One patient reported pain at the final follow-up. Two patients (11.8%) had major complications. One had an extension contracture postoperatively, did not attend therapy, and re-fractured 5 months later requiring reoperation. The second was treated delayed (32 days) and lost fixation, requiring revision surgery and antibiotics for a superficial infection. Two patients with delayed treatment (32 and 44 days) had an extensor lag (11.8%). Conclusions: Operative treatment of mallet fractures with subluxation or involving more than one-third of the articular surface appears effective. Pin removal 4 weeks postoperatively appears adequate. Complications occurred with delayed presentation and non-compliance.